Impact of Employee Training and Strategic Alliances on Business Innovation and Survival - GARAVITO HERNÁNDEZ, Youseline; MANTILLA DUARTE, Carlos Alfonso; RUEDA GALVIS, Javier Francisco; URIBE BERMUDEZ, Johanna Marcela (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In recent years, the academic literature has demonstrated the importance of analyzing the level of employee training and strategic organizational alliances, as determining factors that contribute significantly to innovation and business survival. Based on factor analysis and the Cox regression model with information from 5,623 spanish manufacturing companies, this article shows that companies that link employees with a doctoral level and promote organizational alliances, especially with universities, achieve a higher level of innovation. Their products and consequently better conditions for business survival. RESUMEN En los últimos años, la literatura académica ha demostrado la importancia de analizar el nivel de formación de los empleados y alianzas estratégicas organizacionales, como factores determinantes que contribuyen significativamente a la innovación y supervivencia empresarial. A partir de un análisis factorial y del modelo de regresión de Cox con información de 5.623 empresas manufactureras españolas, el presente artículo demuestra que las compañías que vinculan empleados con nivel doctoral y alianzas estratégicas con universidades, logran un mayor nivel de innovación y mejores condiciones para la supervivencia empresarial.